Whole genome resequencing data sets of different species from Pistacia genus - Tajabadi, Ali (BMC Res Notes, 2021)
OBJECTIVES: Pistacia genus belongs to the flowering plants in the cashew family and contains at least 11 species. The whole-genome resequencing data of different species from Pistacia genus are described herein. The data reported here will be useful for better understand the adaptive evolution, demographic history, genetic diversity, population structure, and domestication of pistachio. DATA DESCRIPTION: Genomic DNA was isolated from fresh leaves and used to construct libraries with insert size of 350 bp. Sequence libraries were made and sequenced on the Illumina Hiseq 4000 platform to produce 150 bp paired-end reads. A total number of 4,851,118,730 billion reads (ranging from 33,305,900 to 34,990,618 reads per sample) were created across all samples. We produced a total of 727.67 Gbp data which have been deposited in the Genome Sequence Archive (GSA) database with the Accession of CRA000978. All of the data are also available as the sequence read archive (SRA) format in the National Center for Biotechnology Information (NCBI) with identifier of SRP189222, mirroring our deposited data in GSA.